In situ temperature measurements in the upper troposphere and lowermost stratosphere from 2 decades of IAGOS long-term routine observation - Berkes, Florian; Neis, Patrick; Schultz, Martin G.; Bundke, Ulrich; Rohs, Susanne; Smit, Herman G. J.; Wahner, Andreas; Konopka, Paul; Boulanger, Damien; Nédélec, Philippe; Thouret, Valerie; Petzold, Andreas (Atmospheric Chemistry and Physics, 2017)
Despite several studies on temperature trends in the tropopause region, a comprehensive understanding of the evolution of temperatures in this climate-sensitive region of the atmosphere remains elusive. Here we present a unique global-scale, long-term data set of high-resolution in situ temperature data measured aboard passenger aircraft within the European Research Infrastructure IAGOS (In-service Aircraft for a Global Observing System; http://www.iagos.org). This data set is used to investigate temperature trends within the global upper troposphere and lowermost stratosphere (UTLS, < 13 km) for the period of 1995–2012 in different geographical regions and vertical layers of the UTLS. The largest number of observations is available over the North Atlantic. Here, a neutral temperature trend is found within the lowermost stratosphere. This contradicts the temperature trend in the European Centre for Medium-Range Weather Forecasts (ECMWF) ERA-Interim reanalysis, in which a significant (95 % confidence) temperature increase of +0.56 K decade−1 is found. Differences between trends derived from observations and reanalysis data can be traced back to changes in the temperature difference between observation and model data over the period studied. This study underpins the value of the IAGOS temperature observations as an anchor point for the evaluation of reanalyses and its suitability for independent trend analyses.